PI‐PD controller design for time delay systems via the weighted geometrical center method. Issue 5 (29th April 2019) - Ozyetkin, Munevver Mine; Onat, Cem; Tan, Nusret
Abstract: In this study, a PI‐PD controller tuning method is presented using the weighted geometrical center method, which is based on the calculation of the weighted geometric center of the stability region obtained by the stability boundary locus method. The proposed method for tuning of PI‐PD controller parameters ( k d, k f, k p and k i ) is performed in three steps. In the first step, the ( k d, k f ) parameter region for the inner loop with PD controller is obtained, and then the weighted geometric center of this region is calculated. In the second step, the inner PD loop is reduced to a single block using the numerical values of ( k d, k f ) that are obtained in the first step. Then, the ( k p, k i ) values of the external loop with PI controller are determined by the same procedure. This tuning method has some advantages over other tuning methods in terms of simplicity and robustness. The simulation examples show that a PI‐PD controller designed using the proposed method provides good performance results when compared to other tuning methods presented in the literature.